The strangers [videorecording (DVD)] : prey at night - Hendricks, Christina, 1975-; Madison, Bailee, 1999-; Henderson, Martin, 1974- (Strangers film series, 2018)
A family of four staying at a secluded mobile home park for the night are stalked and then hunted by three masked psychopaths.